2017
DOI: 10.1515/jtim-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Post-intensive care syndrome: An overview

Abstract: Survival of critically unwell patients has improved in the last decade due to advances in critical care medicine. Some of these survivors develop cognitive, psychiatric and /or physical disability after treatment in intensive care unit (ICU), which is now recognized as post intensive care syndrome (PICS). Given the limited awareness about PICS in the medical faculty this aspect is often overlooked which may lead to reduced quality of life and cause a lot of suffering of these patients and their families. Effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
330
0
41

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(425 citation statements)
references
References 31 publications
10
330
0
41
Order By: Relevance
“…In most of these, PICS has been reported to occur in 25% of ICU survivors, but some studies have reported an even higher incidence, occurring in more than three quarters of ICU survivors [12, 28, 30]. It has been shown that several factors—that is, false memories related to delirium or trauma, use of some medications such as benzodiazepines, circadian rhythm sleep disorders, and phases of impaired alertness during the hospitalization—can determine a worse perception of HRQoL after an ICU hospitalization, favouring the risk of PICS [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these, PICS has been reported to occur in 25% of ICU survivors, but some studies have reported an even higher incidence, occurring in more than three quarters of ICU survivors [12, 28, 30]. It has been shown that several factors—that is, false memories related to delirium or trauma, use of some medications such as benzodiazepines, circadian rhythm sleep disorders, and phases of impaired alertness during the hospitalization—can determine a worse perception of HRQoL after an ICU hospitalization, favouring the risk of PICS [31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the SF-12 and on the clinical evaluation at 6 months, patients were divided in those having and not having evidence of PICS. For the purpose of this study, patients with PICS were identified as those with PCS < 30 and/or MCS < 30, plus clinical evidence of new or worsening impairment in physical, cognitive, or mental health status, as assessed during the 6-month follow-up visitation [28]. The second questionnaire was a previously validated one specifically developed for the follow-up plan of ICU patients (Figure 2) [29].…”
Section: Methodsmentioning
confidence: 99%
“…Частота розвитку ІС у хворих нейрореанімаційних відділень складає 60-98%. В його основі лежить поліорганний сімптомокомлекс м'язово-скелетних (зниження синтезу білків м'язів, м'язова атрофія, зниження м'язової сили і толерантності до навантажень, вкорочення зв'язкового апарату, м'язові контрактури, зниження щільності кісткової тканини, декубітаційні виразки), респіраторних (ателектазованих, пневмонія, зниження максимального тиску вдиху і формованої життєвої ємності легень), ендокринно-метаболічних (інсулінорезистентність зниження активності ренін-ангіотензинової системи, збільшення продукції натрійуретичного пептиду) [8,9].…”
Section: Yurivorokhta@gmailcomunclassified
“…The main risk factors relevant to PICS include delirium duration in ICU, acute brain disorders (e.g., alcoholism, stroke), hypoxic status [due to acute respiratory distress syndrome (ARDS) or cardiac arrest], hypotension (involving severe sepsis and trauma), glucose deregulation, prolonged mechanical ventilation (MV) needed to correct respiratory failure, use of renal replacement therapy, and past history of cognitive impairment combined with advanced age, pre-existing cognitive deficits, or pre-morbid health conditions (Davydow et al, 2012;Carlson and Huang, 2013;Rawal et al, 2017;Iwashyna et al, 2010;Mikkelsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PICS is recently recognised as a public health burden associated with neuropsychological and functional impairments, however its exact prevalence is still vague (Rawal et al, 2017;Wergin and Modrykamien, 2012). Cognitive impairment has been documented to occur in more than 75% of ICU survivors Pandharipande et al, 2014;Davydow, 2013).…”
Section: Introductionmentioning
confidence: 99%